2018
DOI: 10.1016/j.partic.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mesoscale effects in high-shear granulation through a computational fluid dynamics–population balance coupled compartment model

Abstract: In high shear granulation it has been pointed out that there is a need for meso-scale resolution and coupling between flow field information and the evolution of particle properties. In this article we develop a modelling framework that compartmentalizes the high shear granulation process based on process relevant parameters both in time and space. It is built up by a coupled flow field and population balance solver and is used to resolve and analyze the effects of meso-scales on the evolution of particle prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The population balance equations were firstly presented by Hulburt and Katz [16] in 1964, calculating the particle size distribution of the dispersed phase. Since then, the Population Balance Model (PBM) has been popularly introduced to particles in process modelling (e.g., the granulation [17][18][19] and crystallization [20] processes), to investigate the way of change in biomass particle size distribution. Basic mechanisms of the PBM for evolution of the particle size distribution are: nucleation, growth, aggregation and breakage [21].…”
Section: Introductionmentioning
confidence: 99%
“…The population balance equations were firstly presented by Hulburt and Katz [16] in 1964, calculating the particle size distribution of the dispersed phase. Since then, the Population Balance Model (PBM) has been popularly introduced to particles in process modelling (e.g., the granulation [17][18][19] and crystallization [20] processes), to investigate the way of change in biomass particle size distribution. Basic mechanisms of the PBM for evolution of the particle size distribution are: nucleation, growth, aggregation and breakage [21].…”
Section: Introductionmentioning
confidence: 99%
“…Later work by Randolph and Larson , and Timm numerically solved PBEs with more advanced nucleation models, , accounting for variations in both supersaturation and magma density. Their analysis found that numerical solutions became difficult as the order of exponent on supersaturation with the nucleation model increases. ,,, In subsequent years, numerical solution techniques have become far more robust and sophisticated. Nevertheless, there are practical advantages to analytic PBE solutions, where they can be obtained.…”
Section: Introductionmentioning
confidence: 99%